Development Based on Cloud Accounting as Accountant Reconciliation Media on Collage - Williams, Alexander; Dolan, Ellen (Pandawan Sejahtera Indonesia, 2020)
In the process of academic activities, has staff that are structured in an organizational structure to provide excellent service. With the aim of succeeding all activities that are running, and having their respective functional duties, one of them is the head of finance. The head of finance is obliged to report all income and expenses that are needed by collages. Where the financial statements are reported monthly to top management such as the Director of Perguruan Tinggi Raharja The financial report can be said to be accurate if it has passed the final process of reconciliation. Reconciliation is an adjustment of the balance between bank balances and transaction data that we have. There are 8 (eight) financial statement processes until finally Reconciliation is carried out. However, the flow of the reconciliation process can be said to be still semi-conventional and lack the use of existing technology. In this study, 3 (three) problems were identified regarding the reconciliation process which had an impact on the accuracy of financial statements. Where in the reconciliation process accountants enter payment data input and data matching manually so that it requires a long time in the balance balance amount. With financial reports that are faster and more accurate, of course the work can be assessed as effective and efficient according to the time specified. The use of cloud accounting in the reconciliation process is expected to better assist accountants in real terms. So that in the process of reconciliation the accountant gets a financial report that is accurate and effective and efficient in time. This research is of course motivated by accountants in reconciliation activities that are still manually at College. Problems like this, with the use of cloud accounting in financial reports, are a new breakthrough for Perguruan Tinggi Raharja. By conducting 5 (five) literature reviews on reconciliation and cloud accounting to help the performance of accountants in obtaining financial reports. The final result of this study is the implementation of a cloud accounting system at collages in reconciliation activities by accountants.